Calculation of transport characteristics of Yukawa systems by molecular dynamics method - Kodanova, S.K.; Djienbekov, N.E.; Bastykova, N.Kh.; Issanova, M.K. (Recent Contributions to Physics, 2023)
In this paper, the transport characteristics of two-dimensional systems has been investigated. Modeling by means of the Yukawa potential, in a wide range of values of the nonideality parameter, has been carried out. The Yukawa potential was chosen because of its wide applicability in the description of screened interactions in plasmas and other systems. A molecular dynamics method was used to determine the transport characteristics. The study was carried out with the aim of expanding the knowledge of heat transfer in two-dimensional systems. The paper presented the results of numerical experiments in which the dependences of the heat transfer and viscosity coefficients on the screening and non-ideality parameters in systems with Yukawa potential were studied. The obtained data can also serve as a basis for further theoretical and experimental studies in the field of transport characteristics of two-dimensional systems. These data not only expand the understanding of the peculiarities of two-dimensional systems, but also can be useful in the design and analysis of nanostructures and various microdevices.